2011
DOI: 10.1016/j.ydbio.2010.12.037
|View full text |Cite
|
Sign up to set email alerts
|

A role for Zic1 and Zic2 in Myf5 regulation and somite myogenesis

Abstract: Zic genes encode a conserved family of zinc finger proteins with essential functions in neural development and axial skeletal patterning in the vertebrate embryo. Zic proteins also function as Gli co-factors in Hedgehog signaling. Here, we report that Zic genes have a role in Myf5 regulation for epaxial somite myogenesis in the mouse embryo. In situ hybridization studies show that Zic1, 2, and 3 transcripts are expressed in Myf5-expressing epaxial myogenic progenitors in the dorsal medial dermomyotome of newly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 45 publications
2
33
0
Order By: Relevance
“…In all the primary cell cultures [BA (brown adipocytes), ingWA (inguinal white adipocytes), and eWA (epididymal white adipocytes)], Ucp1 expression was induced by NE and rosiglitazone treatment, in accord with earlier studies (Fig. 1B) (26,28,40). In cultured brown adipocytes (BA), Ucp1 was increased to similar mRNA levels in the presence of acute NE or of chronic rosiglitazone (Fig.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…In all the primary cell cultures [BA (brown adipocytes), ingWA (inguinal white adipocytes), and eWA (epididymal white adipocytes)], Ucp1 expression was induced by NE and rosiglitazone treatment, in accord with earlier studies (Fig. 1B) (26,28,40). In cultured brown adipocytes (BA), Ucp1 was increased to similar mRNA levels in the presence of acute NE or of chronic rosiglitazone (Fig.…”
Section: Resultssupporting
confidence: 88%
“…Encircled points were excluded from the analysis. expression of Zic1 is in line with its expression during embryonic development, which is restricted to the most anterior somites (26). This anatomic restriction of Zic1 expression can also explain its absence in mBAT and prBAT, as these are the most posterior BAT(-like) depots (Fig.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…This analysis identified myotome/somite, craniofacial elements, and heart (enrichment scores 2.78, 2.24 and 1.71, respectively). Myotome/somite markers and heart markers were found primarily in the upregulated set, consistent with expression of zic2b in zebrafish somites (Toyama et al, 2004) and with the demonstrated function for mammalian Zic2 during myogenesis (Inoue et al, 2007; Pan et al, 2011). In contrast, craniofacial markers appeared among transcripts depleted in zic2 mutants.…”
Section: Resultssupporting
confidence: 74%
“…In particular, zic1/zic4 have been well investigated in the context of neural development (Aruga et al, 2002;Elsen et al, 2008;Grinberg et al, 2004). However, despite previous descriptions of skeletal and muscular defects in the mouse Zic1 mutants (Aruga et al, 1999;Pan et al, 2011), the role of zic1/zic4 in somite-derived tissues had remained largely unknown. In this study, we took advantage of the medaka Da mutant, an enhancer mutant for zic1/zic4, and have provided experimental evidence that the dorsal characteristics of the fish trunk, such as fin, body shape and pigmentation pattern, are orchestrated by Zic1/Zic4 in the somite.…”
Section: Discussionmentioning
confidence: 99%